The smoking status and the perspective on Law No. 4207 of café, coffee-house, and restaurant owners on the busy streets of central district of Kars (Annals of Medical Research, 2024)
Aim: Making indoor environments 100% smoke-free is the only proven way to protect people from passive smoking. This study aimed to evaluate the smoking status of café, coffeehouse, and restaurant owners and their views on Law No. 4207, which prohibits tobacco use in indoor public spaces, considering sociodemographic variables and the COVID-19 pandemic period.Materials and Methods: The cross-sectional study population comprised 131 café, coffeehouse, and restaurant owners located on busy streets in the central district of Kars.Results: 72 restaurants, 45 cafés, and 14 coffeehouses owners participated to the study. Among the employers don’t allow smoking in the indoor areas of their businesses is 82.4%. Among the 85 smokers, 65.9% did not feel compelled to smoke in prohibited areas, and 57.0% viewed the indoor smoking ban positively. Of the 125 business owners who reported financial loss during the COVID-19 pandemic, 61.6% cited the country's economic situation as the primary reason. In the logistic regression analysis showed that a positive view of the law was 2.69 times higher among employers with high school education or above compared to those with middle school education or lower (95% CI: 1.01-7.2, p=0.049), 3,96 times higher those who did not allow smoking indoors at their workplace compared to those who did (95% CI: 1.28-12.23, p=0.017), and 10.98 times higher among those who stated that the law did not cause financial loss compared to those who stated it did (95% CI: 3.34-36.07, p
Keywords: Smoking; Restaurant; Law; Secondhand smoke